Convergence of fiscal policies in the euro area - Olivier De Bandt; Francesco Paolo Mongelli (European Central Bank (ECB), 2000)
This paper aims at determining whether economic, financial and monetary integration on the one hand, and institutional factors on the other, may have led to gradual convergence in key fiscal variables across the euro area over the recent period, bringing fiscal positions closer together. The Maastricht convergence criteria have facilitated this process but we investigate here whether the structural factors bringing fiscal positions closer together have been a feature of European integration starting already in the 1970s. The alternative scenario is that the euro zone is still characterised by largely idiosyncratic national fiscal policies. Over the 1970-1998 period we run contemporaneous cross-correlation, dispersion and cointegration tests using annual data for government net lending, and total current revenue and expenditure to uncover common trends, as measures of fiscal convergence. We also investigate whether the short term fiscal position in a given country shares both a common euro area component and national features (i.e., idiosyncratic national cycles) using a dynamic factor analysis on quarterly data for the four largest euro area countries since 1985. We find convincing evidence that for euro area countries cross-correlation has increased steadily over the sample period and that fiscal dispersion has been declining at a sustained pace among all countries in the sample. There is evidence of cointegration across the euro area for several countries on the basis of total current revenue, and also for total current expenditure. However, when the series are corrected for the business cycle, cointegration is only accepted for net lending. There is clearly common fiscal cycles for net lending across the euro area that do not only express common business cycles. However, while countries have followed more similar policies in the 1990s in particular during the run-up to EMU, the timing of fiscal adjustment differed across countries. In addition, idiosyncratic components still contribute to a significant share of the variability of individual countries.
Keywords: H60; E61; C22; 330